The Modes of Gaseous Combustion - Rubtsov, Nickolai M.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides an analysis of contemporary problems in combustion science, namely flame propagation, detonation and heterophaseous combustion based on the works of the author. The current problems in the area of gas combustion, as well as the methods allowing to calculate and estimate limiting conditions of ignition, and flame propagation on the basis of experimental results are considered. The book focuses on the virtually inaccessible works of Russian authors and will be useful for experienced students and qualified scientists in the area of experimental studies of combustion processes.
Keywords: Thermodynamics; Heat engineering; Heat transfer; Mass transfer; Fluid mechanics; Physical chemistry; Engineering Thermodynamics, Heat and Mass Transfer; Engineering Fluid Dynamics; Physical Chemistry